2009
DOI: 10.1099/mic.0.031807-0
|View full text |Cite
|
Sign up to set email alerts
|

The Azospirillum brasilense Sp7 noeJ and noeL genes are involved in extracellular polysaccharide biosynthesis

Abstract: The Azospirillum brasilense Sp7 noeJ and noeL genes are involved in extracellular polysaccharide biosynthesis Azospirillum brasilense is a plant root-colonizing bacterium that exerts beneficial effects on the growth of many agricultural crops. Extracellular polysaccharides of the bacterium play an important role in its interactions with plant roots. The pRhico plasmid of A. brasilense Sp7, also named p90, carries several genes involved in synthesis and export of cell surface polysaccharides. We generated two S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 83 publications
2
25
0
Order By: Relevance
“…The data obtained in the present study provide a physiological rationale for the increased stress resistance of flocculated cells and highlight a role for clumping as a transitional and preparatory behavior for resistance to metabolic stress. Both clumping and flocculation are characterized by changes in the adhesive properties of cell surfaces, including changes in the nature of the EPS produced (7,10,35,36). The results obtained here are consistent with these previous findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The data obtained in the present study provide a physiological rationale for the increased stress resistance of flocculated cells and highlight a role for clumping as a transitional and preparatory behavior for resistance to metabolic stress. Both clumping and flocculation are characterized by changes in the adhesive properties of cell surfaces, including changes in the nature of the EPS produced (7,10,35,36). The results obtained here are consistent with these previous findings.…”
Section: Discussionsupporting
confidence: 92%
“…Our data indicate that clumping cells ready their physiology for subsequent nitrogen limitation by preparing for nitrogen fixation. In contrast to clumping, flocculation is a process triggered by metabolic stress, and it involves significant morphological changes, including a loss of motility, increased accumulation of PHB granules, and increased EPS production, representing a reorganization of the cell's physiology more profound than that caused by clumping (8,9,13,20,(34)(35)(36). Numerous studies have linked flocculation with resistance to various stresses, since mutations that abolish or reduce flocculation also impair stress endurance (20,(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…The AZO-core contains genes whose involvement in biosynthesis of exopolysaccharide (EPS) and lipopolysaccharide (LPS) was demonstrated, such as noeL , noeJ and rmlD [7,28]; however, the presence of several unique genes suggests that EPS and LPS components might differ from one Azospirillum strain to another, a feature previously reported for LPS [7]. Only A. brasilense strains possess additional clusters of ancestral genes involved in EPS biosynthesis and/or transport (such as AZOBR_p310279, AZOBR_p330029, AZOBR_p60088, AZCBG_p60114, AZCBG_230032).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, it has been demonstrated that in vitro secretion of GAPDH by E coli varies according to the composition of nutrients in the growth medium [44]. Mannose-6-phosphate isomerase [45] and glutamate dehydrogenase [46] (GDH; COG0334) each have been shown to contribute to microbial survival in the face of oxidative stress. Mannose-6-phosphate isomerase, periplasmic ABC transporters, and phosphomannomutase are involved with processing of extracapsular polysaccharides such as LPS [45], [47].…”
Section: Resultsmentioning
confidence: 99%